Teachers quality as correlates of students learning outcomes in physics in Osun State, Nigeria (2016)
This study investigated teacher qualities as correlates of student achievement and attitude to Physics among secondary school students in Osun State. A random sampling technique was employed for selecting 55 senior secondary (public and private) schools from two local government areas in Osun State. The sample consisted of 1166 Physics students and 55 Physics teachers. Four instruments were used to gather information. T-test analysis was used as the statistical tool for this study and the findings revealed that the learning outcomes of students do not depend on the qualities of teachers considered which include, qualification of teachers, teaching experience, teachers' use of instructional methods, teachers' use of instructional materials and teachers gender. The study recommended therefore that teachers should be rewarded for their performance. Government should work hand-in-hand to fund secondary schools so as to make learning environment conducive. Parents should not force their children to study the Sciences.